1936
DOI: 10.1136/bmj.1.3921.412
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Endocarditis Due to Brucella Abortus

Abstract: when new buildings were under construction. The operation was delayed for, several months while the throat department was being finished. When the surgical quarters became available only four out of forty waiting children required operation. Sutcliffe has observed similar improvement at the Sea Bathing Infirmary at Margate in the health of children waiting for operations which subsequently proved needless. Danischevsky, the honorary secretary of the Russian Committee on Rheumatism, also writes2: " Infection [w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1945
1945
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Endocarditis is a well recognized though rare complication of brucellosis and only four bacteriologically proven cases have been reported in the United Kingdom (Bassett-Smith, 1906;Rennie and Young, 1936;Hart, Morgan, and Lacey, 1951;Grant and Stote, 1953). The world-wide incidence of brucella endocarditis is much more difficult to assess as reports vary.…”
Section: Discussionmentioning
confidence: 99%
“…Endocarditis is a well recognized though rare complication of brucellosis and only four bacteriologically proven cases have been reported in the United Kingdom (Bassett-Smith, 1906;Rennie and Young, 1936;Hart, Morgan, and Lacey, 1951;Grant and Stote, 1953). The world-wide incidence of brucella endocarditis is much more difficult to assess as reports vary.…”
Section: Discussionmentioning
confidence: 99%
“…Undulant fever is not a rare disease in this country; yet endocarditis due to Brucella organisms has only twice been recorded here (Rennie and Young, 1936;Hart et al, 1951), and only in the latter case was it confirmed bacteriologically at necropsy. Dalrymple-Champneys (1950), in his series of 983 cases of undulant fever, does not record a single example.…”
mentioning
confidence: 86%
“…19 The association between endocarditis and brucellosis has been known for at least 80 years. 20 Brucella melitensis infection is linked to the majority of cases of endocarditis in brucellosis patients, although B. abortus has been associated with a small percentage of cases. 17 The most frequently affected valve is the aortic valve 17,[21][22][23] and histology has indicated the large vegetations on valves are the result of direct invasion of the endocardium by bacteria.…”
Section: Human Morbidity and Mortalitymentioning
confidence: 99%